2019
DOI: 10.1097/acm.0000000000002340
|View full text |Cite
|
Sign up to set email alerts
|

Creating GridlockED: A Serious Game for Teaching About Multipatient Environments

Abstract: Further playtesting will be needed to fully examine learning opportunities for various populations of trainees and for various media. GridlockED may also serve as a model for developing other games to teach about processes in other environments or specialties.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“… 76 , 80 82 Gamification is another active learning technique, which involves the utilization of games and competition to support learning. 83 As a technique, gamification may support learning of skills, 84 emergency department (ED) throughput, 83 decision-making, 85 and medical knowledge. 86 89 …”
Section: Overall Conference Structurementioning
confidence: 99%
“… 76 , 80 82 Gamification is another active learning technique, which involves the utilization of games and competition to support learning. 83 As a technique, gamification may support learning of skills, 84 emergency department (ED) throughput, 83 decision-making, 85 and medical knowledge. 86 89 …”
Section: Overall Conference Structurementioning
confidence: 99%
“…Based on the situational game teaching mode, the research by Weidong, et al [30] on physical education teaching revealed that the role of stimulus response selection and implementation in sports tactical decision-making, which proved part of the results obtained in this study, such as reasonable organization in the teaching process. Tsoy, et al [31] in view of the research on the role of team games in teaching, revealed the positive role of game teaching in promoting people's communication. Reasonable game links and content settings help to improve the relationship between people and promote team cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…It can also be done in different formats such as digital, card, and board games (20). The benefits of serious games on learners include enhancing their collaborative awareness via multiplayer settings, providing them with opportunities for active learning to better solve clinical problems, and improving their clinical reasoning, decision-making skills, clinical performance, and the like (5,21,22). As such, serious games have potential alternatives for supplementing traditional simulation-based education and contributing to better academic performances of medical students (23).…”
Section: Serious Games In Medical Educationmentioning
confidence: 99%